Disaster Preparedness and Management Practices in Academic Libraries in Context - Chigwada, Josiline; Ngulube, Patrick (TDMRC, Universitas Syiah Kuala, 2024)
Academic libraries are faced with natural and man-made disasters that can affect service delivery and loss of life to staff and patrons. The study was done to discuss the disaster preparedness and management practices to be observed by academic libraries and identify the enabling and disabling factors towards the successful management of the experienced disasters. The study was conducted as a systematic literature review where articles were retrieved using relevant keywords from Emerald, Sage, Scopus, Web of Science, and Google Scholar where 8753 articles were identified, and 39 articles were reviewed after screening. Using the content analysis approach, the practices that should be factored in disaster preparedness and management plans were analysed. The findings showed that academic libraries were affected by fires, floods, digital disasters, earthquakes, cyclones, typhoons, storms, tornadoes, COVID-19, pest infestation, vandalism, theft, unstable electric power, war, and bomb threats. The disaster preparedness and management practices employed included risk assessment, emergency response planning, staff training, collection protection, digital preservation, backup and recovery, communication and outreach, and collaboration and partnerships. The enabling and disabling factors were funding, awareness, infrastructure, staffing, and collaboration. The authors recommend that academic libraries should have disaster preparedness plans, collaborate and establish partnerships, invest in technology and infrastructure, train both staff and users on dealing with disasters, and insure the library buildings and collections. The study would inform academic library administrators, policymakers, and disaster management professionals in academic institutions about effective strategies that can used to deal with disasters.